The impact of technology changes on productivity in pulp and paper industry - Muhamad Jasmin, Muhamad Hashimi (2014)
In pulp and paper industry, technological changes are critical factors to improve productivity and increase production capacity. The aim for this study is to identify the impacts of technology changes on productivity in pulp and paper industry. Pascorp Paper Industry Sdn Bhd which is the field of study for this research has gone through several technology changes and improvement in their company. New paper machine (PM3) was installed in 2011 to increase production capacity and expand market. The impact and factors of technology changes can be identified through the data obtained from the interview at the company. Results from the interview shows that new technology or technology upgrades do increase Pascorp Paper's productivity in term of production and production capacity. Factors affecting decision to add new technology or to upgrades existing technology such as increasing demands are discussed in this study